Sourcing human capital for organizational effectiveness: sourcing strategy, determinants, and alignment. Issue 5 (9th March 2023) - Bendickson, Joshua S.; Chandler, Timothy D.; James, Barclay E.; Taylor, Erik C.
Abstract: Human capital sourcing is a major determinant of firm effectiveness. We develop logic that favors a specialized sourcing strategy in which organizations emphasize one type of sourcing, focusing either on developing or acquiring human capital, as opposed to a balanced approach. We then identify characteristics and capabilities that lead firms to adopt one sourcing type over another. Additionally, we examine whether aligning sourcing decisions with organizational characteristics and capabilities relates to better performance. We use panel regression to examine how sourcing decisions ultimately impact performance. Results suggest that specialized sourcing relates to improved performance more strongly than does a balanced approach, that certain organizational capabilities are advantageous for specific types of sourcing, and that aligning sourcing strategy with organizational fit partially relates to greater organizational performance.